Penggunaan Pektin Kulit Jeruk Kuok Kampar sebagai Edible Coating Terhadap Kualitas Buah Belimbing Manis Selama Penyimpanan - Jamiatul Khairiyah; Raswen Efendi; Netti Herawati (Agricultural Faculty, 2021)
Kuok orange peel was containing pectin can be used as an edible coating. This research aimed to measured pectin concentration in making of edible coating to protect the surface of the starfruit for longer storage and maintained the quality. The treatment in this research was the concentration of pectin on edible coating, such as without coating (P0), pectin concentration 1% (P1), 2% (P2), 3% (P3), 4% (P4). Sampel storaged at room temperature on 0, 4, 8, and 12 days. The results showed that the edible coating from Kuok orange peel significantly affected weight loss, vitamin C, hardness, total dissolved solids, and sensory assessment to colour and hardness with descriptive nor hedonic. The best treatment was edible coating with pectin concentration 4%, can extended the storage up to 12 days with shrinkage weight amounted to 8.80%, can retain the vitamin C content of 20.03 mg/100g, 1.55 kgf/cm2 of hardness, 15.87% of brix total dissolved solids, and sensory assessment in descriptive at 12 days storage time for colour 2.57(yellow), and hardness 2.60 (soft), and sensory assessment in hedonic for colour 3.17 (rather favoured), hardness 3.13 (rather favoured).